P230 Do we need a "two week rule" referral pathway for lung cancer?. (2nd December 2011) - Ali, M H; Berry, A; Van Griethuysen, J; Peters, H; Jameel, A; Haji, G; Shora, F; Berry, M P; Bowen, E F
Abstract : Introduction: The introduction of the two week rule (TWR) cancer referral system aimed to expedite the diagnosis and treatment of patients with lung cancer. There have been concerns that the system may even lead to delays and there remains little evidence to support its use. We therefore used prospective data to assess the effectiveness of this system. Methods: We prospectively collected data on patients referred in 2010 with suspected lung cancer to a large West London lung cancer centre. We evaluated final diagnosis, performance status, lung cancer staging, time until seen in specialist clinic and time until first treatment for patients referred under the TWR compared with patients referred via our in-house abnormal radiology referral service. Results: In total 249 patients were included in the study (181 from radiology reporting and 68 from GP referrals via the 2 week wait). 83 (33%) cancers were diagnosed from a total of 249 referrals. Patients referred from the radiology department were significantly more likely to have a diagnosis of lung cancer (73/181, 40%) than patients referred under the TWR (10/68, 15%; p<0.001). The mean time from date of referral to seeing a specialist was similar in both groups. All patients diagnosed with lung cancer referred through the TWR had an abnormal chest radiograph. More patients with a performance status 0–1 and earlier stage disease were referred from radiology than through the TWR. Conclusions: A robust radiology referral system is an effective alternative method to diagnosing lung cancer than the TWR. Patients referred from radiology are significantly more likely to have lung cancer. We propose that out-patient clinic slots are reserved for urgent radiology referrals rather than all being allocated to TWR appointments amenable to direct GP bookings. More work is needed to develop this referral pathway further.